Non-equilibrium Feshbach association of Fermionic 6Li atoms - Simmonds, Guy (2020)
In this thesis, an experiment capable of producing 105 6Li2 molecules at temperatures between 0.1-1 µK will be presented. By ﬁrstly loading 108 6Li atoms into a Magneto-Optical Trap (MOT) and transferring them to a far-red detuned optical dipole trap, 106 atoms are loaded at a temperature of 400 µK. Evaporative cooling techniques are used to further cool the cloud to the region of quantum degeneracy. Feshbach coils capable of producing ﬁelds up to 1200G are also implemented to exploit the broad Feshbach resonance between the |F = 1/2,mF = ±1/2> states of 6Li.